Metabolic engineering of B. subtilis 168 for increased precursor supply and poly-γ-glutamic acid production - Halmschlag, Birthe; Völker, Frederik; Hanke, René; Putri, Sastia P.; Fukusaki, Eiichiro; Büchs, Jochen; Blank, Lars M. (Frontiers in Food Science and Technology, 2023)
Poly-γ-glutamic acid (γ-PGA) is an emerging biopolymer produced by several Bacillus species. To improve γ-PGA synthesis, metabolic engineering of the production host B. subtilis poses great potential and is facilitated by the convenient genetical amenability of the organism. In this study, a 3.7-fold increase in γ-PGA production using a bdhA, alsSD, pta, yvmC, and cypX deletion mutant with blocked by-product synthesis pathways was obtained. A detailed analysis of intracellular metabolites for reference strains and the γ-PGA-producing deletion strain identified the accumulation of pyruvate and acetyl-CoA in deletion mutants, highlighting the citrate synthase activity as an important metabolic engineering target for further metabolic flux optimization towards γ-PGA synthesis. An in-depth analysis of growth and γ-PGA production with on-line measurement techniques revealed significant variations across cultivations with deletion mutants that are likely caused by culture acidification due to pyruvate accumulation. Despite the observed acidification, the by-product deletion mutants outperformed the reference strains independent of the promoter controlling the PGA synthetase expression. The constructed deletion strains exhibit high γ-PGA production in minimal medium with glucose as sole carbon source as well as in modified Medium E reaching γ-PGA concentrations of 0.57 gL-1 and 14.46 gL-1, respectively. The results presented in this work broaden the understanding of the microbial metabolism during γ-PGA production and will be useful to guide future metabolic engineering for improved γ-PGA production.